Intracellular delivery and biodistribution study of CRISPR/Cas9 ribonucleoprotein loaded bioreducible lipidoid nanoparticles. (31st July 2018) - Li, Yamin; Bolinger, Justin; Yu, Yingjie; Glass, Zachary; Shi, Nicola; Yang, Liu; Wang, Ming; Xu, Qiaobing
Abstract : A combinatorial library of cationic lipidoids were used as nanocarriers for intracellular delivery of the CRISPR/Cas9 ribonucleoprotein complex. Abstract : CRISPR/Cas9 ribonucleoprotein (RNP) complexes with transient therapeutic activity and minimum off-target effects have attracted tremendous attention in recent years for genome editing and have been successfully employed in diverse targets. One ongoing challenge is how to transport structurally and functionally intact Cas9 protein and guide RNA molecules into cells efficiently and safely. Here we report a combinatorial library of disulfide bond-containing cationic lipidoid nanoparticles (LNPs) as carrier systems for intracellular Cas9/sgRNA delivery and subsequent genome editing. Nanoparticles with high efficacies of targeted gene knockout as well as relatively low cytotoxicities have been identified through in vitro screening. The in vivo biodistribution profiles were studied utilizing fluorescent dye labeled and RNP complexed LNPs. Results from this study may shed some light on the design of effective cationic lipidoids for intracellular delivery of genome editing platforms, as well as optimizing the nanoparticle formulations for further disease modeling and therapeutic applications.